BIOMIMETIC PHOTODIODE DEVICE WITH LARGE PHOTOCURRENT RESPONSE USING PHOTOSYNTHETIC PIGMENT-PROTEIN COMPLEXES - Kusuma, Damar Yoga; Soetedjo, Hariyadi (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2017)
Efficient light to energy conversion was demonstrated in solid-state, lateral photodiodes device containing photosynthetic light-harvesting chlorophyll protein complexes as active materials. The device exhibits the highest reported photocurrent density response of 365 ÂµA/cm2 when illuminated at 320 mW/cm2 radiation source power. The photocurrent response was stabled over 104 s of continuous cycles of dark and illumination states. The short rise and decay time of the photocurrent waveform within sub-second range indicates an effective photogeneration and charge extraction within the device. Optical bandgap extraction using absorption coefficient method reveals that the energy gap of the active materials ranges from 2.8 to 3.8 eV, correspond to the Photosystem I and Photosystem II of the photosynthetic pigment-protein complexes.